2016
DOI: 10.1007/s11356-016-8260-2
|View full text |Cite
|
Sign up to set email alerts
|

Control of the pollution of antibiotic resistance genes in soils by quorum sensing inhibition

Abstract: To investigate whether pollution from antibiotic resistance genes (ARGs) could be affected by bacterial quorum sensing, the oxytetracycline (OTC)-containing manure was fertilized to establish the ARG-polluted soil environment. Under long-term OTC stress, substantial ARGs in the range from 10 to 10 RG/16S rRNA (resistance genes/16S rRNA) were detected in the antibiotics control (AC) group, in which OTC-containing manure was fertilized. Meanwhile, 10 RG/16S rRNA was detected in biological control (BC) group, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It has been reported that quorum sensing is involved in regulating drug resistance of bacteria (Liang et al, 2016 ; Xue et al, 2016 ; Yufan et al, 2016 ; Lai et al, 2017 ), but few studies have investigated the regulation of stress resistance by quorum sensing or LuxS. Quorum sensing facilitates the stress resistance of E. coli in microcapsules by detecting the expression of luxS /AI-2 system (Gao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that quorum sensing is involved in regulating drug resistance of bacteria (Liang et al, 2016 ; Xue et al, 2016 ; Yufan et al, 2016 ; Lai et al, 2017 ), but few studies have investigated the regulation of stress resistance by quorum sensing or LuxS. Quorum sensing facilitates the stress resistance of E. coli in microcapsules by detecting the expression of luxS /AI-2 system (Gao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, LuxS may affect bacterial multi-drugs resistance via complicated regulation mechanisms. In this study, we used oxytetracycline whose resistance was reported to be affected by LuxS, to combine with inhibitor (−)-dimethyl (−)-2,3- O -isopropylidene- l -tartrate and to value its bacteria-killing activity [ 69 ]. Thus, a cocktail of OXY and the inhibitor may be an efficient strategy for antimicrobial therapy and blocking AI-2 biosynthesis.…”
Section: Discussionmentioning
confidence: 99%